2021
DOI: 10.1097/spv.0000000000001110
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Recovery After Urogynecologic Surgery: A Survey of Patient Experience

Abstract: ObjectivesThe aim of this study was to identify which aspects/components of the enhanced recovery program (ERP) were associated with a positive patient surgical experience for patients undergoing urogynecologic surgery.MethodsA total of 198 patients who underwent pelvic reconstructive surgery requiring hospital admission were invited to complete questionnaires modeled after the validated Consumer Assessment of Healthcare Providers and Systems Surgical Care Survey patient experience survey. Patients were asked … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…As programs such as the Hospital Readmissions Reduction Program expand to POP surgery, 30day hospital readmission will grow in importance in a pay-for-performance health care system because it serves as a surrogate marker for quality and safety. Enhanced recovery after surgery (ERAS) protocols decrease multiple-day hospital admissions, postoperative pain, and adverse events and have been successfully applied in urogynecology, [13][14][15][16] thus making same-day discharge a viable option for women undergoing POP surgery. In both single-site and large multisite studies, same-day discharge has been shown to be a safe alternative to next-day discharge (with sim-ilar readmission and ED rates) with high patient satisfaction.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…As programs such as the Hospital Readmissions Reduction Program expand to POP surgery, 30day hospital readmission will grow in importance in a pay-for-performance health care system because it serves as a surrogate marker for quality and safety. Enhanced recovery after surgery (ERAS) protocols decrease multiple-day hospital admissions, postoperative pain, and adverse events and have been successfully applied in urogynecology, [13][14][15][16] thus making same-day discharge a viable option for women undergoing POP surgery. In both single-site and large multisite studies, same-day discharge has been shown to be a safe alternative to next-day discharge (with sim-ilar readmission and ED rates) with high patient satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…In both single-site and large multisite studies, same-day discharge has been shown to be a safe alternative to next-day discharge (with sim-ilar readmission and ED rates) with high patient satisfaction. 2,4,7,15 Currently, the evidence that same-day discharge is safe in older women undergoing POP surgery is limited, and without clear safety data, implementation may be limited. Surgeons may believe that this older group is at higher risk of complications 17 and readmission, and as a result, some surgeons may be reluctant to implement same-day discharge protocols for this cohort of patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations